Toxoplasmosis in HIV/AIDS patients in Malaysia - Nissapatorn, V.; Lee, C.K.C.; Cho, S.M.; Rohela, M.; Anuar, A.K.; Quek, K.F.; Latt, H.M. (2003)
Three hundred and one sera of HIV/AIDS patients were tested for anti-Toxoplasma IgG antibody by ELISA technique. The seroprevalence of toxoplasmosis was 41.2 (95CI: 35.5-46.9) in HIV/AIDS patients. The seroprevalence was significantly higher in the Malay (57.9) than the Chinese (38.7), followed by the Indian patients (29.6) (p<0.05). No possible risk factor, such as contact with cats, consumption of uncooked meat, and history of blood transfusions was found to have any significant association with the presence of anti-Toxoplasma antibody in the study sample (p > 0.05). Multivariate analysis was employed to find any association between Toxoplasma seroprevalence and a single subject having single or multiple risk factors. It was found that the association was not statistically significant (p>0.05). Among the HIV/AIDS study samples, 124 (41.2) samples were found to have positive anti-Toxoplasma antibody, the association between the presence of anti-Toxoplasma antibody and CD4 cell count was determined but no statistically significant association was found (p>0.05). During the study period, only one case of active CNS toxoplasmosis was registered and the diagnostic criteria included: clinical presentations, CT scan finding, serological evidence of anti-Toxoplasma IgG antibody, and respose to anti-Toxoplasma therapy.